PROJECT CONCEPTION OF CAE-SYSTEM FOR WEAR ANALYSIS OF FRICTION BEARING UNDER CONDITIONS OF SHAFT AND LINER AXIS MISALIGNMENT - SOKOLAN, Iuliia; MYLKO, Volodymyr; TKACHUK, Vitaliy; SOKOLAN, Kateryna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Modelling of wear processes is an important stage in the design of mechanisms. Such virtual studies allow predicting the service life of components and the machine as a whole. Modern algorithms of CAE-systems allow performing such analysis with high accuracy and taking into account not only material and operating conditions of the mechanism, but also errors that occurred during the manufacturing and assembly of a particular part. These parts require high requirements to the accuracy of manufacturing and assembly, but within the tolerances of the fields errors of mutual positioning are still allowed, which in turn can significantly affect the service life of the mechanism. Therefore, the task of modeling the wear process of the shaft and sleeve in conditions of mutual misalignment of the axes is relevant. Such sliding pairs exist in almost all machines, including car engines, power generation turbines, etc.In this article it is offered to use the module-integrated approach for modeling of wear processes in tribotechnics, providing use of CAE-systems for definition of functioning conditions of friction units as a system core, and construction of separate modules which in this or that degree are integrated into existing CAE systems. to define values of wear of elements of friction pairs that allows to consider mutual influence of wear and change of functioning conditions in the course of operation.The practical implementation of the module-integrated approach is shown by the example of solving the problem of radial plain bearings wear during the misalignment of the shaft and bush axes in the ANSYS environment. The module of representation of multidimensional matrixes of static or dynamic data, providing essential increase in speed of data processing and quality level of the further analysis of the visualized information from any subject area, is developed.
Keywords: modeling; friction; CAE-systems; wear of machine parts; mutual misalignment of axes; bearing; software